Analisis Semiotika dalam Cerpen Klasik “The Doll’s House” karya Katherine Mansfield - Shafna Chairunnisa (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study analyzes signs and symbols in Katherine Mansfield’s short story “The Doll’s House” (1922) using Charles Sanders Peirce’s semiotic approach. The study is descriptive qualitative in nature, employing data collection techniques such as close reading and note-taking. The analysis was conducted by classifying signs based on Peirce’s theory, icons, index, and symbols, through the triadic model (representamen, object, interpretant). The results of the analysis indicate that the doll’s house functions as both an icon and a symbol of social status and the false luxury of the upper class. Elements such as the smell of paint and the appearance of the Kelvey sisters serve as indices of social inequality. Meanwhile, the small lamp is the strongest symbol representing hope, warmth, and the possibility of transcending social class boundaries. Through this short story, Mansfield critiques class prejudices learned from childhood while conveying a message of empathy across social classes.